Women, men, and society - Renzetti, Claire M.; Curran, Daniel J. (Boston : Allyn and Bacon, 1999)
This book is divided into three parts: Women and Men: What's the difference?; Teaching us to know our respective places; and Keeping us in our respective places.
Keywords: United States; Social conditions; Women; Socialization; Sex role; Sex role -- United States; Sexism -- United States; Women -- Socialization -- United States; Women -- United States -- Social conditions